STRUKTUR MODAL DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DEVIDEN SEBAGAI PEMODERASI PADA PERUSAAHAAN INDUSTRI JASA YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Agam Mei Yudha; Yamasitha Yamasitha; Chintya Ones Charli (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
This study aims to determine and analyze the influence of Capital Structure and Profitability on Firm Value with Dividend Policy as a Moderating Variable. Capital Structure and Profitability are used as independent variables and Firm Value as the dependent variable. And Dividend Policy as a moderating variable. The population in this study is service industry companies listed on the Indonesia Stock Exchange for 2017-2021 with a total of 70 companies or 350 financial reports. In determining the sample using Purposive Sampling method. The data used is secondary data and the analytical method used is panel data method. The results of the research test show that the Capital Structure partially influences firm value. Profitability partially has no effect on firm value. Meanwhile, Dividend Policy as a moderating variable is unable to moderate Capital Structure on Firm Value. Dividend Policy as a moderating variable is able to moderate Profitability on Firm Value. The author advises companies, especially investors, to pay attention to existing risks, the results of this study are expected to be taken into consideration in managing company performance and providing good information for investors